Outcomes and dose-volume parameters for computed tomography-based brachytherapy planning for vaginal recurrence of uterine cancer primarily treated with surgery - Keiko Nemoto Murofushi; Reiko Tanaka; Ayako Ohkawa; Haruko Numajiri; Toshiyuki Okumura; Hideyuki Sakurai (IMR Press, 2021)
Background: This study aimed to evaluate the clinical outcomes and dose-volume parameters of computed tomography CT-based brachytherapy for the vaginal recurrence of uterine cancer after hysterectomy. Methods:　We evaluated 22 uterine cancer patients treated with CT-based brachytherapy for vaginal recurrence between December 2010 and August 2015. Interstitial brachytherapy (ISBT) was used when the vaginal tumor was thicker than 5 mm and/or located at extended extravaginal tissue, whereas intercavitary brachytherapy was performed if it was 5 mm or thinner. Results: Overall, 11 patients had cervical cancer, and 11 had endometrial cancer. The median pretreatment tumor size on magnetic resonance imaging was 17 mm (range, 0-45 mm). Four patients had vaginal recurrence recognized only in the gynecological examination. The primary location of recurrence was the vagina, with extravaginal extension observed in 9 patients. Seventeen patients (77%) received external beam radiotherapy and brachytherapy. ISBT was performed in 12 patients (55%). The median clinical target volume (CTV) D90 was 69.2 Gy (62.6-72.8 Gy). The median D2cc of the bladder, sigmoid, and rectum were 70.2 (63.8-77.6), 37.4 (30.0-43.6), and 52.8 Gy (38.6-63.5 Gy), respectively. Complete response was reached in all patients. The 5-year overall survival rate and local control rate (LC) were 84.8 and 95.5%, respectively. No patient experienced grade ≥3 complications. Conclusions: CT-based brachytherapy has the potential to become an essential treatment for vaginal recurrences of uterine cancer after hysterectomy as it can achieve good LC without increasing the rate of late complications for selected patients with less recurrences.